2005
DOI: 10.2223/jped.1273
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with acute pharyngitis

Abstract: 4.000 g, constituiu-se na variável dependente. Os potenciais preditores da macrossomia foram avaliados através de análise estratificada e da técnica de regressão logística não-condicional, que estima a odds ratio (OR) e os respectivos intervalos de confiança (IC 95%). RESULTADOS: A incidência de ganho de peso gestacional excessivo foi de 29,1%, variando de 10% em mulheres com < 20 anos a 63,6% em mulheres que geraram filhos com macrossomia. A incidência geral de macrossomia foi de 4,8%, sendo de 10,4% para os … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
1
0
1
Order By: Relevance
“…However, when data were present in the medical record, such as prepregnancy weight or the height of the participant, these were obtained by trained and certified interviewers, according to the protocol of the study. Previous studies have shown strong correlations between self-reported weight and measured weight (Ejzenberg & Velásquez-Meléndez, 2005;Gunderson, Abrams, & Selvin, 2000;Han, Abrams, Sridhar, Xu, & Hedderson, 2016;Lederman & Paxton, 1998;Oken, Taveras, Kleinman, Rich-Edwards, & Gillman, 2007). Another limitation can be considered, the monitoring of the participants was by telephone.…”
Section: Discussionmentioning
confidence: 99%
“…However, when data were present in the medical record, such as prepregnancy weight or the height of the participant, these were obtained by trained and certified interviewers, according to the protocol of the study. Previous studies have shown strong correlations between self-reported weight and measured weight (Ejzenberg & Velásquez-Meléndez, 2005;Gunderson, Abrams, & Selvin, 2000;Han, Abrams, Sridhar, Xu, & Hedderson, 2016;Lederman & Paxton, 1998;Oken, Taveras, Kleinman, Rich-Edwards, & Gillman, 2007). Another limitation can be considered, the monitoring of the participants was by telephone.…”
Section: Discussionmentioning
confidence: 99%
“…34 Resultados similares foram encontrados no estudo de coorte de Kac e Velásquez-Meléndez, em 2005, realizado no município do Rio de Janeiro, no qual a maioria das puérperas apresentou ganho de peso gestacional insuficiente. 35 No entanto, o inverso também tem sido documentado, como o estudo com gestantes atendidas no pré-natal de baixo risco no município de São Paulo, em 2007, que encontrou ganho de peso excessivo em 40% delas. 8 Sobre o estado nutricional gestacional, um estudo de coorte com gestantes atendidas em um serviço público de pré-natal em Pernambuco, no ano de 2006, detectou 26,3% das gestantes com excesso de peso, de acordo com o IMC para Idade Gestacional.…”
Section: Discussionunclassified